Priestesses and Patriarchy – The Daily Lives of Ancient Greek Priestesses - Paczuska, Anna (My University, 2017)
This project examines the lives of Greek priestesses in their prominent roles in the patriarchal society of ancient Greece. I argue that priestesses were distinguished from other contemporary women by their performance of roles in major public temples as rulers or ritual officiators, despite being dominated by authoritarian men. A woman in ancient Greece was typically considered a silent agalmata, a prized possession of her male kin (Llewellyn-Jones 2003). Tragedy and myth even flirt with the appropriateness of the sacrifice of women to further the careers of their male relatives (Euripides). Women were expected to adhere to strict standards of decorum, which embodied Greek male preoccupation with visible aidos. Respect or shame of the woman reflected directly on the status of her man. The common woman was thought of as “Aphrodite’s tortoise” at home and in public, concealed behind her shell. Yet the dichotomy between the female and the male (Strauss Clay 2009) activated these priestesses to win a certain level of public status and respect for themselves. These women, including the Pythia, Theano, Iphigenia, and Charicleia, were given the opportunity to be set apart. It is these women, and the active role they played in male society as officials and masters of their temples, that my project investigates.
Citation: Paczuska, A. (2017). Priestesses and Patriarchy – The Daily Lives of Ancient Greek Priestesses. Initials: Student Research Forum, April 21, 2017. Manhattan, KS.
Keywords: Ancient Greece; Priestesses; Patriarchy; Women; Family; Patriotism